ĐA DẠNG DI TRUYỀN CỦA TẬP ĐOÀN GIỐNG XOÀI TẠI VÙNG ĐỒNG BẰNG SÔNG CỬU LONG - Ngo?c, Va?ng Qua?ng; Thành, Võ Công (Tạp chí Khoa học Đại học Cần Thơ, 2005)
Mango species in theMekong Delta ofViet Nam was considered as in the region of original center of polyembryo mangoes (Vo Cong Thanh andHuynhKy, 2000). A twelve economic mango varieties propagated by seeds such as ?Cat Chu?, ?Thanh ca?, ?Thom? planting in the region,six mango varieties in the germplasm of Cantho University were also analysed by leaf protein (SDS-PAGE) and DNA (CAPS-PCR run with 5 primer: CAP1A, CAP3A, CAP3B, CAP5A, CAP12A) methods. Results showed that any young leaf samples in the same tree had the same proteins,a sexual plant could distinguish with asexual plants by leaf protein method easily. CAP5A could be applied to distinguish polyembryos into one sexual and asexual embryos. Mango varieties such as ?Du Du?, ?Thom?, ?Buoi?, and ?Hon? were clasified into the same group (M.odorata). Other varieties including ?Bac?, ?Cat Chu?, ?Cat?, ?Tuong?, ?Cat Hoa Loc? were M. indica, and ?Thanh Ca? variety has confirmed as M. mekongensis (Pham Hoang Ho 2001). Đồng Bằng Sông Cửu Long nằm trong vùng khởi nguyên của cây xoài trồng. Xoài là loại cây ăn trái vừa có phẩm chất ngon, vừa thích hợp với thị hiếu của người tiêu dùng, do đó nó có giá trị cao về mặt kinh tế. Với kỹ thuật điện di protein (bằng phương pháp SDS-PAGE) và điện di ADN (primer CAP 5A) đã nhận diện được cây lai và cây phôi tâm của 6 giống xoài: Trung Quốc, Martin, Cát Vân Đen, Cát Hòa Lộc, Phim Xẻng Măng, Namdorkmai. Kết quả điện di protein cũng cho thấy các giống: (1) Giống xoài Bưởi, Đu Đủ, Hòn và Thơm thuộc loài Mangifera odorata; (2) Giống xoài Cát, Cát Chu, Lai, Cát Hòa Lộc, Tượng và Bắc thuộc loài Mangifera indic; (3) Giống xoài Thanh Ca thuộc loài Mangifera mekongensis.